A report on palaeontological excavations and sampling in mudrocks: some guidelines - Walter Etter (Swiss Journal of Palaeontology, 2024)
Abstract More than 60% of the world’s sedimentary rocks are mudrocks (Potter et al., 1980; Schieber, 1998; Potter, 2003; the term mudrock is favored here over mudstone because the latter term was used to characterize a limestone texture; Dunham, 1962). From a palaeontological perspective these are, compared to sandstones and limestones, heavily undersampled. The main reason for this is that mudrocks decay in surface exposures to small chips, which develop with sun/heat and rain into an awkward pulp. The decay of the mudstone concomitantly destroys all macrofossils which are not durable. This comprises fossils with an aragonitic or delicate calcitic shell unless they are preserved as pyritic or internal calcitic molds or preserved within calcareous concretions. Therefore, most of the fossils are not recorded in surface exposures. In addition, sedimentologic investigations of mudrocks are hampered because (i) compaction makes sedimentary structures hardly recognizableand (ii) good thin sections of mudrocks are exceedingly difficult to manufacture. For micropalaeontological investigations, mudrocks rich in organic material are especially difficult to process. Standard treatments with boiling water, sodium carbonate solution, or peroxide H2O2 generally fail to dissolve much of the sediment so that the fine fraction (and in mudrocks we usually need the 63μm-fraction) largely consists of clay particle aggregates. Yet there are methods to dissolve these aggregates. Otherwise, picking the microfossils would become extremely laborious. In this paper, some guidelines for successful palaeontological work in mudrocks are outlined. These are based on the author’s personal experience. Examples from Jurassic mudrocks of Switzerland/Europe show that such excavations can be very rewarding.